Traffic Congestion Impact on Energy Consumption and Workforce Productivity: Empirical Evidence from a Developing Country - Annan, Jonathan; Mensah, John; Boso, Nathaniel (Archives of Business Research, 2015)
Vehicular traffic congestion is an important public policy issue as it has the potential to impact fuel consumption and workforce productivity levels. As such, scholarly works have focused on explaining key drivers and outcomes of vehicular traffic congestion. Accordingly, this study examines a web of relationships that involves the individual and joint effects of private car usage and mass transportation services on vehicular traffic congestion as well as the impact of vehicular traffic congestion on fuel consumption and workforce productivity. To examine these relationships primary data is obtained from public school teachers in a metropolitan city of Kumasi in Ghana, an emerging Sub-Sahara African economy. The study finds that while private school teachers’ private car usage is associated with increases in road traffic congestion, mass transportation usage does not directly impact traffic congestion levels. A more interesting finding is that high levels of private car usage and increases in mass transport usage jointly impact increases in vehicular traffic congestion. In addition, the study finds that whereas private car usage and vehicular traffic congestion are associated with increases in fuel energy consumption, mass transportation services is found to be associated with greater workforce productivity levels. A key public policy implication is that systematic management of vehicular flow is important for reducing traffic congestion and energy consumption in urban centers and for increasing workforce productivity.